Impact of the Canterbury earthquakes on dispensing of psychiatric medication for children and adolescents: longitudinal quantitative study. (March 2020) - Beaglehole, Ben; Moor, Stephanie; Zhang, Tao; Hamilton, Gregory J.; Mulder, Roger T.; Boden, Joseph M.; Frampton, Christopher M. A.; Bell, Caroline J.
Abstract : Background: Natural disasters are increasing in frequency and impact; they cause widespread disruption and adversity throughout the world. The Canterbury earthquakes of 2010–2011 were devastating for the people of Christchurch, New Zealand. It is important to understand the impact of this disaster on the mental health of children and adolescents. Aims: To report psychiatric medication use for children and adolescents following the Canterbury earthquakes. Method: Dispensing data from community pharmacies for the medication classes antidepressants, antipsychotics, anxiolytics, sedatives/hypnotics and methylphenidate are routinely recorded in a national database. Longitudinal data are available for residents of the Canterbury District Health Board (DHB) and nationally. We compared dispensing data for children and adolescents residing in Canterbury DHB with national dispensing data to assess the impact of the Canterbury earthquakes on psychotropic prescribing for children and adolescents. Results: After longer-term trends and population adjustments are considered, a subtle adverse effect of the Canterbury earthquakes on dispensing of antidepressants was detected. However, the Canterbury earthquakes were not associated with higher dispensing rates for antipsychotics, anxiolytics, sedatives/hypnotics or methylphenidate. Conclusions: Mental disorders or psychological distress of a sufficient severity to result in treatment of children and adolescents with psychiatric medication were not substantially affected by the Canterbury earthquakes.